Sustainable Carbon Materials toward Emerging Applications. Issue 5 (31st March 2021) - Lan, Guojun; Yang, Jing; Ye, Run‐Ping; Boyjoo, Yash; Liang, Ji; Liu, Xiaoyan; Li, Ying; Liu, Jian; Qian, Kun
Abstract: It is desirable for a sustainable society that the production and utilization of renewable materials are net‐zero in terms of carbon emissions. Carbon materials with emerging applications in CO2 utilization, renewable energy storage and conversion, and biomedicine have attracted much attention both academically and industrially. However, the preparation process of some new carbon materials suffers from energy consumption and environmental pollution issues. Therefore, the development of low‐cost, scalable, industrially and economically attractive, sustainable carbon material preparation methods are required. In this regard, the use of biomass and its derivatives as a precursor of carbon materials is a major feature of sustainability. Recent advances in the synthetic strategy of sustainable carbon materials and their emerging applications are summarized in this short review. Emphasis is made on the discussion of the original intentions and various sustainable strategies for producing sustainable carbon materials. This review provides basic insights and significant guidelines for the further design of sustainable carbon materials and their emerging applications in catalysis and the biomedical field. Abstract : Nanostructured carbon materials afford unparalleled potential in catalytic and biomedical applications due to their versatile features. It is critical to sustainably fabricate next generation nanostructured carbon materials for tackling current challenges toward a carbon‐neutral society. In this review, recent developments in the sustainable synthetic strategy of nanostructured carbon materials and their emerging applications in catalysis and biomedical are summarized.